Postoperative Outcomes And Surgical Complications In Typhoid Ileal Perforation: Postoperative Outcomes in Typhoid Ileal Perforation - Katyar, Ishrat Rahim; Khatti, Shah Nawaz; Raza, Ali; Abbas, Khurram; Rizvi, Mohammad Basil; Ahmad, Zeeshan (Pakistan Journal of Health Sciences, 2024)
Surgical repair for typhoid ileal perforation is essential to prevent peritonitis and sepsis. Postoperative outcomes, which include survival rates and recovery times, underscore the importance of comprehending surgical complications to refine treatment strategies and enhance patient survival. Objective: To determine postoperative outcomes and surgical complications in typhoid ileal perforation. Methods: The prospective cohort was conducted at General Surgery Department of Liaquat University Hospital in Hyderabad & Jamshoro. 228 Patients of age 18 years or more and of any gender, who were operated for having single typhoid ileal perforation, were included in the study. While patients with multiple perforations, TB peritonitis or having traumatic perforations, were excluded from the study. Results: The most common age group was found to be 18-30 years (40.4%), followed by 31-40 years (28.1%), 41-50 years (19.3%), 51-60 years (7.9%), and >60 years (4.4%). Males comprised 57.9% of the population, while females made up 42.1%. The mean length of hospitalization was found to be 14 ± 5 days. The majority of patients experienced good outcomes, accounting for 158 individuals (69.3%), while 70 patients (30.7%) had adverse outcomes. Among the adverse outcomes, there was a mortality rate of 7.2% (16 patients) and 54 patients (23.7%) experienced complications, some experienced more than one complication. Conclusions: The study concluded that though the majority of patients recover well, a significant proportion (7.2%) still faced adverse postoperative outcomes in terms of mortality. 54 patients (23.7%) experienced complications, some experienced more than one complication.